Early Spondylotic Changes in Cervical Spine Due to Weight Lifting on Head in Al-Muthanna Governorate - Jabbar Hawala, Usama; Adnan Munshid, Bashar; Shahad Safi , Ali (International Journal of Psychosocial Rehabilitation, 2020)
Objective: Assess the relation between cervical spine degeneration and extrinsic axial load from weights overhead lifting. Methods: Cross-sectional study of sixty patients (all of them were females) between 18 and 70 years of age who complained of neck pain and stiffness between August 2018 and January 2020 in Al Muthanna College of Medicine. The patients were divided into two groups, group (I) head weight carrier and group (II) non-head weight carrier, for comparison in degree of cervical spine degeneration. The cervical spine was evaluated on a lateral radiograph by measuring disc space and vertebral height from the C2-C3 level to the C7-T1 level and using the Gore et al. scoring system to evaluate the degeneration of these levels. Result: The disc space heights of C2-C3, C3-C4, and C7-T1 of group (I) were not significantly different from that of group (II); the heights of C4-C5, C5-C6, and C6-C7 in group (I) were significantly smaller than that of group (II ) with p-values of 0.005, 0.009, and 0.030, respectively. The vertebral height of C3, C4, and C7 of group (I) is not significantly different from group (II); the heights of C5 and C6 of group (I) are significantly smaller than that of group (II) with p-values of 0.011 and 0.048, respectively. The results of the Gore et al. scoring system of C2-C3, C3-C4, and C7-T1 of group (I) were not significantly different from those of group (II), while the scoring of C4-C5, C5-C6, and C6-C7 in group (I) was significantly different from that of group (II ) with p-values of 0.001, 0.008, and 0.009, respectively. Conclusion: Extrinsic load on the cervical spine from head weightlifting causes spine segment degeneration represented by disc space narrowing, decrease in vertebral height, and osteophyte formation. The most affected levels are C4-C5, C5-C6, and C6-C7.